Size Evolution of Silica Nanoparticles in Different Solvents - Liu, Fengguo; Yang, Wangjin; Wang, Ying; Xue, Xiangxin; Yang, He (Asian Journal of Chemistry, 2015)
Monodisperse silica nanoparticles were prepared by a sol-gel method with ultrasonication using tetraethoxy silane (TEOS) as silicon source and ammonia as catalyst in methanol, ethanol and acetone as different solvents. The morphologies of growing silica nanoparticles were observed by transmission electron microscopy (TEM) at different reaction times. The diameter distribution was analyzed statistically by Image J software. The results indicated that the diameter of silica in methanol as solvent was smallest and the uniformity of silica particle size in ethanol as solvent was optimal. The formation mechanisms of the resultant silica nanoparticles in different solvents related to the size evolution were discussed.